Design Portable Health Checker Device with Blood Oxygen Monitor Project - Tariq Morshed Baqir (American Journal of Botany and Bioengineering, 2025)
Portable health checker device it’s the process of looking at a disease, condition, or one or more medical phenomena over time. With rapid medical development of our modern societies, the health care systems are becoming much more mature and professional. In order to reduce the current burden of public health system and promote the popularity of routine health self-check, this technique has been developed for making faster and accurate pre diagnoses with ease-of-use. Pulse test is painless test, that measures a person’s oxygen saturation level, this health checker device is used to check how well the heart is pumping oxygen throughout the body. It can be applied to check the status of the patients with any type of condition, such as pulmonary diseases or COPD, anemia, lung cancer etc. In such patients, diseases may require constant monitoring and care. In order to take care of this issue our system comes to rescue. It is easy to use this portable system which can be carried anywhere by the subject. This health check system is powered by At mega 328 microcontroller which consists of max30100 sensor that measure (blood oxygen, heart rate) and mlx90614 (temperature sensor) LCD and adapter.